2015
DOI: 10.1016/j.matlet.2015.04.085
|View full text |Cite
|
Sign up to set email alerts
|

Irradiation tolerance of amorphous SiOC/crystalline Fe composite

Abstract: a b s t r a c tWe examined the radiation tolerance of amorphous silicon oxycarbide (SiOC) and crystalline Fe composite by using ion irradiation and transmission electron microscopy (TEM). The Fe/SiOC multilayer thin films were grown via magnetron sputtering with controlled length scale on a surface oxidized Si (100) substrate. These alloys were irradiated by 120 keV He þ ions to a damage level of $ 1.3 displacements per atom (dpa) at room temperature. TEM characterization shows neither sign of point defect clu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
18
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 40 publications
(18 citation statements)
references
References 21 publications
0
18
0
Order By: Relevance
“…[13] The developed α-Fe/amorphous SiOC composite showed radiation stability after irradiation to 1.3 dpa at RT where the crystalline/amorphous interface was very effective at annihilating point defects and enhancing radiation tolerance. [14] While the crystalline/amorphous interface in Fe/ SiOC composites has been shown to effectively remove defects, the limit to which Fe/SiOC multilayers can sustain radiation damage remains unclear. Also, how the interface density affects the irradiation stability of the Fe/SiOC layered system needs to be further studied.…”
Section: (Received 3 August 2015; Final Form 30 September 2015)mentioning
confidence: 99%
See 1 more Smart Citation
“…[13] The developed α-Fe/amorphous SiOC composite showed radiation stability after irradiation to 1.3 dpa at RT where the crystalline/amorphous interface was very effective at annihilating point defects and enhancing radiation tolerance. [14] While the crystalline/amorphous interface in Fe/ SiOC composites has been shown to effectively remove defects, the limit to which Fe/SiOC multilayers can sustain radiation damage remains unclear. Also, how the interface density affects the irradiation stability of the Fe/SiOC layered system needs to be further studied.…”
Section: (Received 3 August 2015; Final Form 30 September 2015)mentioning
confidence: 99%
“…The individual layer thickness for thin Fe/SiOC multilayer films is 14 nm. The detailed microstructure characterization of as-deposited Fe/SiOC multilayers can be found in reference [14].…”
Section: (Received 3 August 2015; Final Form 30 September 2015)mentioning
confidence: 99%
“…One example of such a composite is the Fe/SiOC system, which has exhibited promising thermal and radiation tolerant properties. [24][25][26][27] An interesting feature of the Fe/SiOC system is that it is composed of crystalline metal and amorphous ceramic. Previous studies mainly focus on mixing in either crystalline/crystalline or amorphous/amorphous systems.…”
mentioning
confidence: 99%
“…Samaras et al [51] also observed that areas of high free volume within a grain boundary can serve as defect recombination sites. The importance of free volume was reinforced experimentally by Su et al [52], who showed that the interfaces of amorphous SiOC/crystalline Fe multilayers act as efficient point defect sinks.…”
Section: Introductionmentioning
confidence: 94%